2014
DOI: 10.3389/fcimb.2014.00072
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the tryptophan-indole-IFNγ axis on human genital Chlamydia trachomatis infection: role of vaginal co-infections

Abstract: The natural history of genital Chlamydia trachomatis infections can vary widely; infections can spontaneously resolve but can also last from months to years, potentially progressing to cause significant pathology. The host and bacterial factors underlying this wide variation are not completely understood, but emphasize the bacterium's capacity to evade/adapt to the genital immune response, and/or exploit local environmental conditions to survive this immune response. IFNγ is considered to be a primary host pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
80
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 115 publications
(151 reference statements)
3
80
0
1
Order By: Relevance
“…It has been previously shown that Salmonella enterica serovar Typhimurium tryptophan synthase can produce ammonia and pyruvate from serine by a ␤-elimination reaction in the absence of indole (31). We speculate that TrpB P221S may not be able to bind indole but may still be able to produce ammonia, based on a hypothesis that Aiyar and colleagues proposed to explain the inactivation of tryptophan synthase in independent trachoma lineages (31). Future studies will determine if the mutant TrpB is associated with altered catalysis of the serine-indole condensation and ␤-elimination reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously shown that Salmonella enterica serovar Typhimurium tryptophan synthase can produce ammonia and pyruvate from serine by a ␤-elimination reaction in the absence of indole (31). We speculate that TrpB P221S may not be able to bind indole but may still be able to produce ammonia, based on a hypothesis that Aiyar and colleagues proposed to explain the inactivation of tryptophan synthase in independent trachoma lineages (31). Future studies will determine if the mutant TrpB is associated with altered catalysis of the serine-indole condensation and ␤-elimination reactions.…”
Section: Discussionmentioning
confidence: 99%
“…This specimen produced few infectious EBs but contained a high Chlamydia genome load, suggesting that most of the genomes corresponded to persistent organisms (3). The observations described above suggest that C. trachomatis genital strains may rely on microbiome-derived indole to circumvent IDO1-mediated tryptophan depletion (31,32).…”
mentioning
confidence: 99%
“…A major component of the antichlamydial immune response, and the factor that has received the most research attention, is gamma interferon (IFN-␥) (27,28). C. trachomatis is unable to synthesize tryptophan and must obtain this essential amino acid from its host (29).…”
Section: Trachomatis Persistencementioning
confidence: 99%
“…Kod žena sa bakterijskom vaginozom postoji povećan rizik za polno prenosive infekcije uzrokovane Neisseria gonorrhoeae i Chlamydia trachomatis [5], Trichomonas vaginalis [6], virusom Herpes simplex tip-2 (HSV-2) [7], virusom humane imunodeficijencije (HIV) [8], kao i različitim vrstama anaerobnih mikroorganizama koji se u povećanom broju nalaze u vaginalnom sekretu. Nedavne studije ukazuju da izmijenjena vaginalna flora kod žena sa bakterijskom vaginozom utiče na razvoj cervikalne intraepitelijalne neoplazije (CIN) [9], a udružena je i sa prevremenim porođajem i povećanim rizikom za nastanak spontanih pobačaja [10].…”
Section: Uvodunclassified